Pengaruh Mega Influencers dan Media Sosial Marketing Terhadap Keputusan Pembelian dan Kesadaran Merek Sebagai Variabel Mediasi (Studi Kasus Pengikut Scarlett Whitening di Tiktok Shop) - Santy, Raeni Dwi; Aulia, Vinka; Adhim, Mohammad Fauzil (Fakultas Ekonomi dan Bisnis Universitas Komputer Indonesia, 2025)
This study aims to examine the influence of mega influencers and social media marketing on purchase decisions, with brand awareness serving as a mediating variable. A quantitative survey was conducted on 100 followers of the Scarlett Whitening TikTok account using purposive sampling and analyzed with PLS-SEM. The study results indicate that macro influencers and social media marketing have a positive and significant effect on brand awareness, and brand awareness significantly influences purchase decisions. Crucially, brand awareness successfully mediates the entire influence between the two independent variables and purchase decisions. These findings affirm the crucial role of influencer- and social media-based digital strategies in strengthening brand awareness and stimulating consumer purchases